Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fphar.2021.621194
|View full text |Cite
|
Sign up to set email alerts
|

Velvet Antler Ameliorates Cardiac Function by Restoring Sarcoplasmic Reticulum Ca2+-ATPase Activity in Rats With Heart Failure After Myocardial Infarction

Abstract: Objective: Velvet antler (VA; cornu cervi pantotrichum), a well-known traditional Chinese medicine, has been shown to exert cardioprotective effects. The purpose of this study was to investigate the effect of VA on heart failure (HF) caused by ischemia-reperfusion, and explore its possible mechanism from the regulation of sarcoplasmic/endoplasmic reticulum Ca2+-ATPase 2 alpha (SERCA2a).Methods: A rat model of HF was established by ligating the left anterior descending coronary artery of male Sprague–Dawley rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…LC–MS analysis and data mining were processed according to the methods described in the literature. 35 , 36 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…LC–MS analysis and data mining were processed according to the methods described in the literature. 35 , 36 …”
Section: Methodsmentioning
confidence: 99%
“…LC-MS analysis and data mining were processed according to the methods described in the literature. 35,36 Animal Treatments Sixty 7-week-old male Wistar rats weighing (170 ± 10) g (Sippur Will Kay Company) were housed at the Experimental Animal Center of Zhejiang Chinese Medical University (Hangzhou, China, Certificate No. SCXK 2018-0012) and acclimatized for a week under the standard conditions at (24 ± 0.5) °C with 12-hour light-dark cycles, fed standard rodent chow with free access to water.…”
Section: Nano-hplc-ms/ms Analysis Of Jtgmentioning
confidence: 99%
“…Mitochondria play a significant role in adjusting metabolism, generating ROS, and guaranteeing cell activity (Zhang et al, 2019a;Zhang X. et al, 2021). Bcl-2 inhibits apoptosis, whereas Bax promotes it, causing damage to the membrane structure and potential of mitochondria (Wang Q. et al, 2016).…”
Section: Mitochondria-mediated Signaling Pathwaymentioning
confidence: 99%
“…And NF-κB has function of inhibiting anti-apoptotic protein Bcl-2 ( Neamatallah et al, 2018 ). MIRI up-regulates the levels of reactive oxygen species (ROS) and ER stress and further leads to intracellular calcium overload and apoptosis ( Chaudhari et al, 2014 ; Lai et al, 2020 ; Song et al, 2020 ; Shi et al, 2021 ). ROS activates ER stress and JNK to increase the content of ROS ( Chaudhari et al, 2014 ; Son et al, 2014 ; Lu et al, 2017 ; Chu et al, 2019 ).…”
Section: Myocardial Cell Apoptosis In Myocardial Ischemia/reperfusion...mentioning
confidence: 99%
“…Previous reports have indicated that VA had anti‐inflammatory effects on human rheumatoid arthritis fibroblast‐like synoviocytes and alleviated the Parkinson's disease by inhibiting oxidative stress in mice, 17,18 further demonstrating that VA had many beneficial components and pharmacological actions 19–22 . Also, other studies have shown that VA could rescue the sarcoplasmic reticulum Ca 2+ ‐ATPase activity and thus enhanced the cardiac function in rats with heart failure 23,24 . However, whether VA could improve the quality of oocytes under oxidative stress from diverse environmental factors is largely elusive.…”
Section: Introductionmentioning
confidence: 99%